2015
DOI: 10.1080/1067828x.2013.777378
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Adolescent Substance Abuse Programs With Updated Quality Indicators: The Development of a Consumer Guide for Adolescent Treatment

Abstract: When adolescent substance abuse requires treatment, few parents know which treatment features are important and which treatment programs are effective. There are few resources to help them select appropriate care. We describe early work on an evaluation method and comparative treatment guide for parents based upon the premise that the quality of a program and its potential effectiveness is a function of the number and frequency of evidence-based treatment practices (EBPs) delivered. Thus, we describe the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…For AD, indicators of appropriate care (7) were less common than indicators of inappropriate care (21). For cancer, indicators of appropriate (12) and inappropriate (14) end-oflife care were evenly divided. For COPD, indicators of appropriate care (9) were again less common than those of inappropriate care (19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For AD, indicators of appropriate care (7) were less common than indicators of inappropriate care (21). For cancer, indicators of appropriate (12) and inappropriate (14) end-oflife care were evenly divided. For COPD, indicators of appropriate care (9) were again less common than those of inappropriate care (19).…”
Section: Resultsmentioning
confidence: 99%
“…Expert interviews resulted in 32 additional unique indicators. Indicators selected based on literature referred almost equally to appropriate (12) and inappropriate (14) care, while indicators from interviews rarely referred to appropriate care (6) and often referred to inappropriate care (26).…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Community and family support, continuing care, and treatment monitoring of progress are important. Cacciola et al 64 have also identified ten features with 62 discrete practices that are associated with quality substance abuse care (eg, assessment, attention to mental health, comprehensive treatment, family involvement in treatment, developmentally informed programming, engaging and retaining adolescents in treatment, staff qualifications and training, culturally competent care, continuing care and recovery supports, program evaluation). These closely parallel National Institute of Drug Abuse principles.…”
Section: Principles Of Adolescent Substance Use Disorder Treatmentmentioning
confidence: 99%
“…Arguably the biggest advance to date has been the establishment of quality indicators designed to assess broad principles of care such as appropriate treatment assignment, retention and follow-up rates, referrals for medication and ancillary care, and client safety (see Pincus, Spaeth-Rublee, &Watkins, 2011). While useful for delineating basic contours of adequate service delivery (for the latest ASU example see Bekkering et al, 2014; Cacciola et al, 2015; NIDA, 2014), such broad principles of care do not inform the selection and delivery of specific treatment techniques to meet the unique needs of individual clients (Garland et al, 2010; Garland & Schoenwald, 2013). Likewise, the quality indicators used to asses such principles can only verify if a given procedure occurred or a service quota was met; they cannot specify how procedures should be implemented or measure whether services were delivered with acceptable fidelity.…”
Section: Clinical Implications and Utilities Of Distilling Core Elmentioning
confidence: 99%